ALGORITHMIC CENTRAL PLANNING: BETWEEN EFFICIENCY AND FREEDOM. - PAŁKA, PRZEMYSŁAW (Law & Contemporary Problems, 2020)
The author discusses the possible realization of conditions for an efficient planned economy by way of a society's state of technology and the people's socio-technological practices. Topics covered include the preconditions of an efficient and algorithmic centrally planned economy, and the question of preference between the liberal world of market exchange and a world of command and control. Also noted is the role of law in facilitating changes in socioeconomic systems.